Low-cost microfluidics: Towards affordable environmental monitoring and assessment - Mesquita, Pedro; Gong, Liyuan; Lin, Yang (Frontiers in Lab on a Chip Technologies, 2022)
Effective environmental monitoring has become a worldwide concern, requiring the development of novel tools to deal with pollution risks and manage natural resources. However, a majority of current assessment methods are still costly and labor-intensive. Thanks to the rapid advancements in microfluidic technology over the past few decades, great efforts have been made to develop miniaturized tools for rapid and efficient environmental monitoring. Compared to traditional large-scale devices, microfluidic approaches provide several advantages such as low sample and energy consumption, shortened analysis time and adaptabilities to onsite applications. More importantly, it provides a low-cost solution for onsite environmental assessment leveraging the ubiquitous materials such as paper and plastics, and cost-effective fabrication methods such as inkjet printing and drawing. At present, devices that are disposable, reproducible, and capable of mass production have been developed and manufactured for a wide spectrum of applications related to environmental monitoring. This review summarizes the recent advances of low-cost microfluidics in the field of environmental monitoring. Initially, common low-cost materials and fabrication technologies are introduced, providing a perspective on the currently available low-cost microfluidic manufacturing techniques. The latest applications towards effective environmental monitoring and assessment in water quality, air quality, soil nutrients, microorganisms, and other applications are then reviewed. Finally, current challenges on materials and fabrication technologies and research opportunities are discussed to inspire future innovations.